Strengthening Students’ Digital Moral Literacy through Islamic Religious Education (PAI) Learning: A Developmental Psychology Perspective - Muhammad Fadhil Raihan Iryandi; Eva Latipah (Linguanusa : Social Humanities, Education and Linguistic, 2026)
Introduction to the Problem: The rapid development of digital technology has transformed adolescent behavior, creating moral challenges such as cyberbullying, digital addiction, and declining empathy and social responsibility. Islamic Religious Education (PAI) has been identified as a strategic instrument for character formation, yet limited studies have specifically integrated PAI with digital moral literacy in the context of adolescent developmental psychology. Purpose: This study aims to analyze the strengthening of students’ digital moral literacy through PAI learning from a developmental psychology perspective, addressing the gap between moral knowing and digital moral performance among adolescents. Design/Methods/Approach: This qualitative library research employed content analysis of 28 reputable scientific publications (2022–2025) discussing digital moral literacy, PAI, adolescent development, and cyberbullying. Data collection involved identification, selection, and critical review of relevant literature from academic databases. Triangulation of sources and interpretation using moral development, cognitive development, and ecological systems theories were applied. Findings: The study reveals three main findings: (1) a significant critical blind spot exists where 64.3% of articles define digital moral literacy conceptually, yet students demonstrate moral knowing without digital moral performance; (2) innovative PAI strategies including project-based learning, digital storytelling, and Islamic ethical pedagogy (musāwah, ‘adl, raḥmah, karāmah insāniyyah) show effectiveness in developing critical awareness and prosocial behavior; (3) only 25% of articles explicitly integrate developmental psychology frameworks, with no operational design based on developmental stage differences (elementary, junior, and senior high school levels). Research Limitations/Implications: As a library research, this study is limited by the availability and scope of existing literature, without primary empirical data. The findings provide a conceptual framework but require experimental validation. Originality/Value: This study offers a novel conceptual framework integrating PAI, digital moral literacy, and developmental psychology, proposing stage-based pedagogical strategies for different age groups. It provides practical recommendations for curriculumreformulation and teacher competency development.